Blindness And Visual Impairment in Delhi Region - Kishor P Govekar; Mukesh K Sharma (Medsci Publications, 2014)
Introduction: Prevalence of blindness has been very much increased in developed countries like India nowadays. Amongst the causes of blindness, many causes are preventable by routine eye check-up even at primary health centre. Therefore regular eye check-up is the need of time in India. Rapid assessment methods for blindness (RAAB) are recently implied for fast evaluation and epidemiological analysis of blindness in particular region and according to that, a strategic plan can be made to cope with these conditions. Method: We applied same RAAB method to analyse the prevalence of blindness and visual impairment in 5000 people of more than 50years of age residing in Delhi region as a cross sectional study. Results: Most number of cases were from age group between 50 years to 59 years (47.21%). The mean age was 57.2 yrs. Cases were slightly more in male sex. 751 cases were having vision acuity of 3/60 and below. Amongst the causes of blindness, cataract was most common affecting 60.95% cases having vision acuity of <3/60 and 72.98% cases having vision acuity of <6/60. An alarming high prevalence of diabetic retinopathy was found compared to studies done in other regions previously. Conclusion: Most of the causes of blindness seen in our study are preventable if proper awareness and medical facilities for regular eye check-up and treatment.